Overseeding Rhizoma Perennial Peanut Pasture and Hay Fields during the Cool Season - Jose C. B. Dubeux; Cheryl L. Mackowiak; Ann R. Soffes Blount; David L. Wright; Luana Queiroz Dantas (EDIS, 2019)
Hay and livestock producers want to know if they can overseed their rhizoma peanut fields with cool-season forages during rhizoma perennial peanut dormancy. This new 5-page document discusses overseeding for hay and overseeding for grazing. Written by Jose Dubeux, Cheryl Mackowiak, Ann Blount, David Wright, and Luana Dantas, and published by the UF/IFAS Agronomy Department, January 2019. http://edis.ifas.ufl.edu/ag426